Association between phase angle from bioelectrical impedance and dietary intake in athletes: a cross-sectional study - Christianne de Faria Coelho-Ravagnani; Lorena Cristina Curado Lopes; Allan da Mata Godois; Analiza Mónica Silva; Vitor Cordeiro; Adolfo Henrique Costa dos Santos; João Felipe Mota (Journal of Nutritional Science)
Phase Angle (PhA) has emerged as an important parameter to monitor body composition, fluid status, muscle integrity, and physical performance among athletes. However, limited information exists regarding the associations between PhA and dietary intake, especially in athletes. This study aimed to identify the dietary intake components associated with PhA in athletes. This cross-sectional observational study was carried out with 153 athletes across 17 sports. Body composition was assessed by tetrapolar multifrequency BIA, and dietary intake by 24-hour dietary recalls administered on non-consecutive days. Reported foods and supplements were categorised into different groups (i.e. cereals, vegetables, fruits, beans and nuts, meat and eggs, dairy products, oils, and sugars), with portions established based on the food’s total energy content. Fat-free mass and fat-free mass index were higher in male compared to female athletes, potentially influencing PhA (6.6º vs 5.5º; P < 0.01). Multiple linear regression analysis indicated that protein intake was a significant predictor of PhA in athletes. This association remained significant even after adjustments for sex, age, and fat-free mass (R2 = 0.48, β = 0.27, P = 0.02). The positive correlation observed between dietary protein and PhA reinforces the need for adequate daily protein intake to enhance PhA in athletes. Further studies investigating the effect of diet-induced changes in PhA within the athletic population are necessary.